Navigating Open Science as Early Career Feminist Researchers. (December 2021) - Pownall, Madeleine; Talbot, Catherine V.; Henschel, Anna; Lautarescu, Alexandra; Lloyd, Kelly E.; Hartmann, Helena; Darda, Kohinoor M.; Tang, Karen T. Y.; Carmichael-Murphy, Parise; Siegel, Jaclyn A.
Open science aims to improve the rigor, robustness, and reproducibility of psychological research. Despite resistance from some academics, the open science movement has been championed by some early career researchers (ECRs), who have proposed innovative new tools and methods to promote and employ open research principles. Feminist ECRs have much to contribute to this emerging way of doing research. However, they face unique barriers, which may prohibit their full engagement with the open science movement. We, 10 feminist ECRs in psychology from a diverse range of academic and personal backgrounds, explore open science through a feminist lens to consider how voice and power may be negotiated in unique ways for ECRs. Taking a critical and intersectional approach, we discuss how feminist early career research may be complemented or challenged by shifts towards open science. We also propose how ECRs can act as grass-roots changemakers within the context of academic precarity. We identify ways in which open science can benefit from feminist epistemology and end with envisaging a future for feminist ECRs who wish to engage with open science practices in their own research.